MiR-199a-3p-regulated alveolar macrophage-derived secretory autophagosomes exacerbate lipopolysaccharide-induced acute respiratory distress syndrome - Xu, Xinyi; Liu, Xu; Dong, Xuecheng; Yang, Yi; Liu, Ling (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose Acute respiratory distress syndrome (ARDS) is a prevalent illness in intensive care units. Extracellular vesicles and particles released from activated alveolar macrophages (AMs) assist in ARDS lung injury and the inflammatory process through mechanisms that are unclear. This study investigated the role of AM-derived secretory autophagosomes (SAPs) in lung injury and microRNA (MiR)-199a-3p-regulated inflammation associated with ARDS in vitro and in a murine model. Methods The ARDS model in mouse was established by intratracheal LPS lipopolysaccharide (LPS) injection. The agomirs or antagomirs of MiR-199a-3p were injected into the caudal vein to figure out whether MiR-199a-3p could influence ARDS inflammation and lung injury, whereas the mimics or inhibitors of MiR-199a-3p, siRNA of Rab8a, or PAK4 inhibitor were transfected or applied to RAW264.7 cells to evaluate the mechanism of SAP release. Culture supernatants of RAW264.7 cells treated with LPS or bronchoalveolar lavage fluid from mice were collected for the isolation of SAPs. Results We found that MiR-199a-3p was over-expressed in the lungs of ARDS mice. The MiR-199a-3p antagomir alleviated, whereas the MiR-199a-3p agomir exacerbated LPS-induced inflammation in mice by promoting AM-derived SAP secretion. In addition, MiR-199a-3p over-expression exacerbated LPS-induced ARDS via activating Rab8a, and Rab8a silencing significantly suppressed the promoting influence of the MiR-199a-3p mimic on SAP secretion. Furthermore, MiR-199a-3p mimic activated Rab8a by directly inhibiting PAK4 expression. Conclusion The novel finding of this study is that MiR-199a-3p participated in the regulation of SAP secretion and the inflammatory process via targeting of PAK4/Rab8a, and is a potential therapeutic candidate for ARDS treatment.